Symbolism and nostalgia: new house or new life? The architecture of remittances from Jackson Hall, USA, to San Simeon, Mexico - Hernández, Perla Ileana (2023)
The architecture of remittances in San Simeón Xipetzinco, Tlaxcala, is a symbolic representation that evokes nostalgia for its migrants established in the region of Jackson Hall, Wyoming, whom strive to demonstrate economic success. The objective of the study is to showthe feelings of the migrants who do not want to be forgotten by the people who saw themborn and move away to a new life; making themselves present through majestic buildingsthat seek recognition of the community for them and their family. The remittance architecture blends the coldness of a new home with the warmth of the emotions and feelings ofmigrants like Paula and Emilio, who after 20 years of effort and work left Mexico in exchangefor a better quality of life in another country.